2021
DOI: 10.1038/s41467-020-20259-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting USP47 overcomes tyrosine kinase inhibitor resistance and eradicates leukemia stem/progenitor cells in chronic myelogenous leukemia

Abstract: Identifying novel drug targets to overcome resistance to tyrosine kinase inhibitors (TKIs) and eradicating leukemia stem/progenitor cells are required for the treatment of chronic myelogenous leukemia (CML). Here, we show that ubiquitin-specific peptidase 47 (USP47) is a potential target to overcome TKI resistance. Functional analysis shows that USP47 knockdown represses proliferation of CML cells sensitive or resistant to imatinib in vitro and in vivo. The knockout of Usp47 significantly inhibits BCR-ABL and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…Additionally, P22077 eliminated leukemia stem/progenitor cells in CML mice while exhibiting low toxicity to mononuclear cells in normal peripheral blood. Therefore, targeting USP47 is an effective and secure strategy to overcome TKI resistance and eradicate leukemia stem/progenitor cells (Lei et al, 2021).…”
Section: Other Cancersmentioning
confidence: 99%
“…Additionally, P22077 eliminated leukemia stem/progenitor cells in CML mice while exhibiting low toxicity to mononuclear cells in normal peripheral blood. Therefore, targeting USP47 is an effective and secure strategy to overcome TKI resistance and eradicate leukemia stem/progenitor cells (Lei et al, 2021).…”
Section: Other Cancersmentioning
confidence: 99%
“…A few examples of pharmacological DUB inhibitors inducing protein degradation for therapeutic benefit have been reported in hematologic malignancy models, including myeloid neoplasms [265,[352][353][354] and multiple myeloma [353,355,356]. In AML, a recent study showed promising results for destabilization of the FLT3 mutant driver oncoprotein through inhibition of USP10.…”
Section: Are Dubs Possible Therapeutic Targets?mentioning
confidence: 99%
“…Delightfully, most of the CML patients can achieve complete remission after receiving tyrosine kinase inhibitors (TKIs) treatment, and some patients even discontinue the TKIs treatment to achieve treatment-free remission (TFR) [ 21 , 22 ]. However, drug resistance and relapse restrict the application of TKIs in treating CML through BCR-ABL-dependent and -independent mechanism [ 23 ]. The BCR-ABL-dependent mechanism is mediated through BCR-ABL gene amplification, mutation of the ABL kinase domain and MDR1 upregulation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…USP47 is involved in cell survival [ 46 ], cell proliferation [ 47 , 48 ], DNA damage repair [ 23 , 49 , 50 ], epithelial-mesenchymal transition [ 51 ], and inflammation [ 52 , 53 ]. It is demonstrated that Usp47 knockout significantly prolongs the survival of BCR-ABL and BCR-ABL T315I -induced CML mice by reducing leukemia stem/progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation